2014
DOI: 10.1080/21658005.2014.965919
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the Little Owl (Athene noctua) during the pre-reproductive period in a semi-arid Mediterranean region

Abstract: The assessment of feeding conditions and variations in diet composition over the pre-breeding period of birds plays a keyrole in the understanding of reproductive performance. Pellets regurgitated by the Little Owl, Athene noctua, were collected from Boulhilet (Batna, north-east Algeria). The analysis of 48 pellets resulted in the identification of 471 preyitems of 38 different species classified into 6 classes, 7 orders, 21 families, and 35 genera. Although the diet of the Little Owl mainly consists of arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
(24 reference statements)
3
14
0
Order By: Relevance
“…; and (vii) the SRI/S ratio, which varies between 0 and 1. Some diversity parameters (N, S, RF) were expressed at the level of taxonomic orders to facilitate comparisons with previous studies (Chenchouni 2014(Chenchouni , 2017.…”
Section: Data Analysis: Diversity Parametersmentioning
confidence: 99%
“…; and (vii) the SRI/S ratio, which varies between 0 and 1. Some diversity parameters (N, S, RF) were expressed at the level of taxonomic orders to facilitate comparisons with previous studies (Chenchouni 2014(Chenchouni , 2017.…”
Section: Data Analysis: Diversity Parametersmentioning
confidence: 99%
“…Remnants of Mus species, often representing a significant source of food (Chenchouni 2014), were found in all of the sampling sites, where livestock farms located within the territory of the owl. However, unlike in other studies carried out in Hungary (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…House Mouse proved to be also numerous in sites where farm buildings are redundant (Apaj and Kunpeszér). In such environments, synanthropic small mammals can have a considerable contribution in the diet (Marián & Schmidt 1968, Romanowski et al 2013, Chenchouni 2014. It has also been observed that Little Owls hunt for these preys inside the buildings (Genot & Van Nieuwenhuyse 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian presence in the diet of Little Owl is usually scarce (Lanszki 2006, Romanowski et al 2013, Chenchouni 2014 or completely absent , Hounsome et al 2010, Šálek et al 2010 depending their availability and the habitat. Although occasional reports on presumed higher proportions of amphibian prey are available (Uttendörfer 1939, Festetics 1955, this phenomenon has rarely been observed.…”
Section: Hámori Gy Szél and D Winklermentioning
confidence: 99%